Household modelling and trade-off analysis to design resilient crop- livestock farming systems in dry regions of Senegal - Kumar, Shalander; Pramanik, Soumitra; Yessofou, Adjani Nourou-Dine; Worou, Omonlola Nadine; Anthony, Whitbread (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This paper analyzes integrated crop-livestock farming systems in dryland regions of Senegal using household survey data and whole farm household modeling. It focuses on the Kaffrine and Thies regions, which exhibit differences in cultivated land area, staple crops grown, and livestock holdings. The analysis identifies region-specific opportunities to sustainably enhance productivity, resilience, and food security. The mechanistic model incorporates factors like crop mixes, livestock herd dynamics, climate impacts, economics, and labor to simulate entire farms. It finds crops generating most of the household income in the more crop-focused Thies region versus only about one-third in livestock-centric Kaffrine, where nearly half of incomes are from small ruminants. Three resilience enhancing interventions were evaluated in the model – i. introducing improved cattle, ii. farmer participation in climate smart agriculture (CSA) and climate information services (CIS) program, and iii. Combining intervention scenario-i and intervention scenario-ii. Introducing improved cattle have over twice the marginal impact on farm cashflows in cattle- dominant Kaffrine compared to crop-focused Thies. Farmers participation in CSA and CIS program raises their incomes in comparable percentages in both regions given the broad importance of crops. Pursuing integrated crop and livestock interventions yields additive income gains in mixed farming Kaffrine versus specialized Thies. The analysis demonstrates greater opportunities for synergies between crops and livestock in Kaffrine’s mixed system context compared to Thies. It provides empirical evidence to inform agricultural policies and investments tailored to regional production patterns. Overall, the paper shows the value of integrated, context-specific approaches to enhancing productivity, resilience, and food security across Senegal's diverse smallholder systems. The major contribution of this study that the household model has been parameterized for the dryland region of Senegal. We have completed and validated only few initial scenarios. We have also run additional scenarios evaluating the effect of interventions such as introducing small scale home gardening, watermelon, mango, climate information services, improved sowing machine and other climate smart agricultural practices, however these scenarios still need to be validated by the stakeholders, hence not included in this publication.